Accelerating Spirocyclic Polyketide Synthesis using Flow Chemistry1. (11th April 2014) - Newton, Sean; Carter, Catherine F.; Pearson, Colin M.; de C. Alves, Leandro; Lange, Heiko; Thansandote, Praew; Ley, Steven V.
Abstract Over the past decade, the integration of synthetic chemistry with flow processing has resulted in a powerful platform for molecular assembly that is making an impact throughout the chemical community. Herein, we demonstrate the extension of these tools to encompass complex natural product synthesis. We have developed a number of novel flow‐through processes for reactions commonly encountered in natural product synthesis programs to achieve the first total synthesis of spirodienal A and the preparation of spirangien A methyl ester. Highlights of the synthetic route include an iridium‐catalyzed hydrogenation, iterative Roush crotylations, gold‐catalyzed spiroketalization and a late‐stage cis‐selective reduction.